Risk Factors for hypospadias in Northwest Russia: A Murmansk County Birth Registry Study - Kovalenko, Anton Alexandrovich; Brenn, Tormod; Odland, Jon Øyvind; Nieboer, Evert; Krettek, Alexandra; Anda, Erik Eik (PLOS ONE, 2019)
Source at https://doi.org/10.1371/journal.pone.0214213. Background - Hypospadias is the most common congenital anomaly of the penis, but its causes are mainly unknown. Of the risk factors identified, the most plausible are hormonal and genetic. The aim of this study was to identify risk factors for hypospadias in Northwest Russia based on registry data. Methods - The study population included male infants registered in the Murmansk County Birth Registry between 1 January 2006 and 31 December 2011 (n = 25 475). These infants were followed-up for 2 years using the Murmansk Regional Congenital Defects Registry to identify cases of hypospadias not diagnosed at birth. We used logistic regression analysis to examine the contributions of hypospadias risk factors. Results - Out of 25 475 male infants born during the study period, 148 had isolated hypospadias. The overall prevalence rate was 54.2 (95% CI 53.6–54.8) per 10 000 male infants. Those born to mothers with preeclampsia (OR = 1.65; 95% CI 1.03–2.66) or infant birthweight < 2500 g (OR = 2.06; 95% CI 1.18–3.60) exhibited increased risk for hypospadias. Maternal age, smoking during pregnancy, folic acid intake during pregnancy or hepatitis B surface antigen positivity did not associate with increased risk of hypospadias. Conclusions Combining data from a birth registry with those from a congenital defects registry provided optimal information about the prevalence of hypospadias and its association with low infant birthweight and preeclampsia. These factors have in common changes in hormone levels during pregnancy, which in turn may have contributed to hypospadias development.